The acute effects of cannabidiol on emotional processing and anxiety: a neurocognitive imaging study - Michael A. P. Bloomfield; Yumeya Yamamori; Chandni Hindocha; Augustus P. M. Jones; Jocelyn L. L. Yim; Hannah R. Walker; Ben Statton; Matthew B. Wall; Rachel H. Lees; Oliver D. Howes; Valerie H. Curran; Jonathan P. Roiser; et al. (Psychopharmacology, 2022)
Rationale There is growing interest in the therapeutic potential of cannabidiol (CBD) across a range of psychiatric disorders. CBD has been found to reduce anxiety during experimentally induced stress in anxious individuals and healthy controls. However, the mechanisms underlying the putative anxiolytic effects of CBD are unknown. Objectives We sought to investigate the behavioural and neural effects of a single dose of CBD vs. placebo on a range of emotion-related measures to test cognitive-mechanistic models of its effects on anxiety. Methods We conducted a randomised, double-blind, placebo-controlled, crossover, acute oral challenge of 600 mg of CBD in 24 healthy participants on emotional processing, with neuroimaging (viewing emotional faces during functional magnetic resonance imaging) and cognitive (emotional appraisal) measures as well as subjective response to experimentally induced anxiety. Results CBD did not produce effects on brain responses to emotional faces and cognitive measures of emotional processing, or modulate experimentally induced anxiety, relative to placebo. Conclusions Given the rising popularity of CBD for its putative medical benefits, these findings question whether further research is warranted to investigate the clinical potential of CBD for the treatment of anxiety disorders.